2006
DOI: 10.1021/jp0663154
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Uranium Hexachloro Complexes in Room-Temperature Ionic Liquids. A Molecular Dynamics Investigation in Two Liquids

Abstract: We report a molecular dynamics study of the solvation of UCl(6)(-), UCl(6)(2-), and UCl(6)(3-) complexes in the [BMI][Tf(2)N] and [MeBu(3)N][Tf(2)N] ionic liquid cations based on the same anion (bis(trifluoromethylsulfonyl)imide (Tf(2)N-)) and the butyl-3-methyl-imidazolium+ (BMI+) or methyl-tri-n-butyl-ammonium (MeBu(3)N+) cation, respectively. The comparison of two electrostatic models of the complexes (ionic model with -1 charged halides versus quantum mechanically derived charges) yields similar solvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…However, recent calculations on UCl 6 2-complexes with the two types of charges have been shown to yield very similar results. 55 The mutation of UO 2 Cl 4 2-to UO 2 Cl 4 3-was achieved in 21 steps, i.e. with increments ∆λ of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent calculations on UCl 6 2-complexes with the two types of charges have been shown to yield very similar results. 55 The mutation of UO 2 Cl 4 2-to UO 2 Cl 4 3-was achieved in 21 steps, i.e. with increments ∆λ of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…By dissolving uranyl perchlorate in [C 4 mim][NfO] (NfO: nonafluorobutanesulfonate), the formation of a fourfold complex of [UO 2 ] 2+ and OPPh 3 can be detected in the liquid phase by 31 P NMR spectroscopy and in the solid by single‐crystal X‐ray structure analysis 34. Molecular dynamic studies of homoleptic hexachlorido complexes of U V , U IV and U III in [C 4 mim][Tf 2 N] or [N 1114 ][Tf 2 N] reveal that [UCl 6 ] 3– is surrounded by a first coordination shell exclusively formed by [C 4 mim] + or [N 1114 ] + , whereas in the cases of [UCl 6 ] 2– and [UCl 6 ] – , the Tf 2 N – anion is able to enter the first coordination sphere 35. It is noteworthy that [C 4 mim] + shows a stronger interaction with [UCl 6 ] 3– than [N 1114 ] + due to its higher hydrogen bonding capability.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Numerous studies indicated that additional attention should be paid to polarization treatment in systems with high ionic concentrations. 341 While simulations using nonpolarizable models provided important insight into molecular level correlations and structure in ionic systems, 42,43 they also demonstrated that thermodynamic and transport properties predicted from MD simulations are often inconsistent with experiments showing much slower dynamics, with the agreement becoming worse at higher salt concentrations. 4346 For example, recent simulations by Rajupt et al of 3 M lithium bis(trifluoro-methanesulfonyl)imide (referred as NTf 2 or TFSI or TFSA) solution in 1,3-dioxolane and 1,2-dimethoxyethane (DOL:DME) mixture predicted Li + and NTf 2 ion diffusion coefficients more than 100 times slower than experiments.…”
Section: Introductionmentioning
confidence: 99%